DIGITAL CLASSROOM REVOLUTION: A STUDY OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IMPLEMENTATION IN INDONESIAN EDUCATION THROUGH LITERATURE STUDY - Nurjanah; Sulmiah; Ida Saidah; Aprilliantoni (Journal Informatic, Education and Management (JIEM), 2026)
The development of digital technology through the use of ICT has driven educational transformation , especially in supporting the implementation of the Independent Curriculum which emphasizes flexible , innovative , and student- centered learning . This study uses a literature study method by analyzing 15 books and 25 journal articles to examine the application of digital technology , supporting and inhibiting factors , its impact on learning , and the prospects for digital education in Indonesia. The results of the study show that digital technology has transformed traditional learning into a more interactive , collaborative , and learner - oriented one . Although supported by the Independent Curriculum policy , its implementation still faces obstacles such as the digital access gap, limited infrastructure , and low digital literacy of educators . However , the use of technology has been proven to increase student motivation , participation , and learning outcomes . In addition , the development of artificial intelligence and adaptive learning is expected to further support the personalization of learning . The study concludes that the success of the digital classroom revolution requires equal access , increased digital competence , changes educational culture , and sustainable policies to realize adaptive and inclusive education in Indonesia .